Mental health challenges of Tibetan music teachers: A mixed-methods study - Yilun Li; Bo Yang; Yuqi Lin; Shuxiang Hu; Qizong Yue (Acta Psychologica)
The mental health challenges faced by music teachers, particularly in culturally and geographically distinct regions such as Tibet, have garnered increasing attention within the field of education. This study investigates the mental health challenges faced by music teachers in Tibet, employing a mixed-methods approach. Quantitative data from 256 teachers were collected using the SCL-90, BDI, and PHQ-9 scales, revealing significantly higher levels of depression, anxiety, and other mental health issues compared to their counterparts in Southwest China. Qualitative interviews and grounded theory identified key challenges, including personal psychological factors, external pressures such as work-related stress and family expectations, and cultural communication barriers with students and parents. The study highlights the need for targeted psychological interventions and improved support systems to enhance the mental well-being of Tibetan music teachers, emphasizing the importance of addressing both personal and occupational support system to improve their mental health level.